Communication of the absence: possible instruments. On-site communication project for the archaeological area ‘La Cuma’ of Monte Rinaldo - Irina Ivanova (Groma)
The term ‘communication of the absence’ concerns the problem of reconfiguration of the lost architectural volume. The issue regards the archaeological monuments that had mostly reached our days only at the foundations level. On the example of the archaeological area ‘La Cuma’ of Monte Rinaldo the development of the on-site communication project based on a certain methodology is showed. It provides the complex analysis of the monument, the research of study cases, the definition of project vision and the choice of the most effective solutions aimed at giving back a disappeared image of the ancient complex.